1990
DOI: 10.1007/bf01407522
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow during experimental epidural bleeding in swine

Abstract: Regional cerebral blood flow (rCBF) was studied during an aggressive epidural bleed, using a ventilated swine model. rCBF, regional organ blood flow and cardiac output were measured using the radioactive microsphere technique. Blood flows were measured prior to the start of bleeding (Stage 1), when intracranial pressures had reached a plateau and supratentorial perfusion pressure was reduced by about 50% (Stage 2), and at isoelectric EEG (Stage 3). Supratentorial rCBF did not change significantly between stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 38 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…11 In a swine-model of epidural bleeding, ICP gradients was found between the pressure measurement in the lateral ventricles and in the cisterna magna. 12 In this animal model, supra-was higher than infratentorial ICP level, with a pressure gradient ranging from 15 to 33 mm Hg depending on the final mass volume. 12 Supraand infratentorial ICP gradients were also observed in animal models that simulated subdural bleeding.…”
Section: Intracranial Pressure Gradients Between Different Supra-and mentioning
confidence: 99%
See 1 more Smart Citation
“…11 In a swine-model of epidural bleeding, ICP gradients was found between the pressure measurement in the lateral ventricles and in the cisterna magna. 12 In this animal model, supra-was higher than infratentorial ICP level, with a pressure gradient ranging from 15 to 33 mm Hg depending on the final mass volume. 12 Supraand infratentorial ICP gradients were also observed in animal models that simulated subdural bleeding.…”
Section: Intracranial Pressure Gradients Between Different Supra-and mentioning
confidence: 99%
“…12 In this animal model, supra-was higher than infratentorial ICP level, with a pressure gradient ranging from 15 to 33 mm Hg depending on the final mass volume. 12 Supraand infratentorial ICP gradients were also observed in animal models that simulated subdural bleeding. 13 In addition, it could be demonstrated a failure of free communication between the two hemispheres of increased epidural pressure resulting from focal epidural mass lesion as well as incomplete ICP transmission from an intracerebral mass lesion to the overlying subarachnoid space.…”
Section: Intracranial Pressure Gradients Between Different Supra-and mentioning
confidence: 99%
“…It is of note, however, that Griffiths et al 18 demonstrated significant subarachnoid spread of blood following EBP by MRI studies. Therefore, the question arises as to whether EBP, and possibly also subarachnoid leakage of the injectate, 17 does not merely reverse the vasodilatation (due to CSF leak) that causes PDPH. Yucel et al 6 recently suggested that this might well be the case.…”
Section: Discussionmentioning
confidence: 99%
“…Using an extradural balloon as a model of mass lesion in monkeys, Langfitt, et al, 17 demonstrated the existence of gradients and their dependency on the patency of the basal cisterns surrounding the brainstem at the level of the tentorial incisura. In a model of epidural bleeding in swine, Ganz, et al, 13 also demonstrated ICP gradients between the pressures measured in the lateral ventricles and in the cisterna magna. In this model, supratentorial was higher than infratentorial ICP, with a pressure gradient ranging from 15 to 33 mm Hg J. Neurosurg.…”
Section: Gradients Of Icp Between the Supra-and Infratentorial Comparmentioning
confidence: 94%